A Foresight Analysis of Structural Challenges in Implementing Oman’s National Education Strategy 2040 within a VUCA Environment and Human-Centered Artificial Intelligence - Aljaradi, Saif Hamad; Joo, Zahra Rafat; Marzooghi, Rahmatoallh; Torkzadeh, Jafar; Heydari, Elham (Journal of Educational and Psychological Sciences, 2025)
This study aimed to provide a foresight analysis of the structural challenges hindering the implementation of Oman’s National Education Strategy 2040, within the context of a VUCA environment and the transformative impact of human-centered artificial intelligence. The study adopts a qualitative foresight methodology, employing structural content analysis and critical comparison of national strategic documents and institutional reports, alongside a review of selected recent literature (2020–2024). The findings reveal a structural gap between strategic aspirations and current executive systems, and a limited integration of VUCA perspectives and futures thinking into school education policies. Furthermore, the educational system’s organizational structure remains burdened by overlapping mandates and a lack of effective transformative leadership. The study recommends reengineering the school education system towards a flexible, competency-based learning model that enhances the future-readiness of human capital, and developing evaluation and accountability systems based on learning outcomes rather than administrative inputs.